PENGUJIAN FAKTOR YANG MEMPENGARUHI CASH DIVIDEND DAN IMPLIKASINYA TERHADAP NILAI PERUSAHAAN (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
This study examines possible indicators of dividend policy: investment opportunities, profitability, and capital structure. Based on selected indicators, then further tested whether the dividend policy has implications for firm value. The sample of this study is all companies that distributed dividends consistently during 2013 – 2017. This research is a causality study using panel data regression and continued with different tests using chi-square. The results showed that investment opportunities, profitability and capital structure simultaneously have a significant effect on dividend policy. The results of the study prove that profitability has a positive effect on dividend policy. This result indicates that profitable companies will consistently provide dividends. The results also showed that there were no differences in dividend policy between companies that has a high or low value. Thus the results of this study support the irrelevance theory that it does not exist a difference in the value of companies that provide or do not provide dividends.Keywords: dividend, profitability, investment, capital structure